Integrated transcriptome and metabolome profiling of Camellia reticulata reveal mechanisms of flower color differentiation - Geng, Fang; Nie, Ruimin; Yang, Nan; Cai, Lei; Hu, YunChong; Chen, Shengtong; Cheng, Xiaomao; Wang, Zhonglang; Chen, Longqing (Frontiers in Genetics, 2022)
Camellia reticulata (Lindl.) is an important ornamental plant in China. Long-term natural or artificial selections have resulted in diverse phenotypes, especially for flower colors. Modulating flower colors can enhance the visual appeal and economic value in ornamental plants. In this study, we investigated the molecular mechanisms underlying flower color differentiation in C. reticulata. We performed a combined transcriptome and metabolome analysis of the petals of a popular variety C. reticulata (HHYC) (red), and its two cultivars ‘Xuejiao’ (XJ) (pink) and ‘Tongzimian’ (TZM) (white). Targeted metabolome profiling identified 310 flavonoid compounds of which 18 anthocyanins were differentially accumulated among the three samples with an accumulation pattern of HHYC > XJ > TZM. Likewise, transcriptome analysis showed that carotenoid and anthocyanin biosynthetic structural genes were mostly expressed in order of HHYC > XJ > TZM. Two genes (gene-LOC114287745765 and gene-LOC114289234) encoding for anthocyanidin 3-O-glucosyltransferase are predicted to be responsible for red coloration in HHYC and XJ. We also detected 42 MYB and 29 bHLH transcription factors as key regulators of anthocyanin-structural genes. Overall, this work showed that flavonoids, particularly anthocyanins contents are the major determinants of flower color differentiation among the three C. reticulata samples. In addition, the main regulatory and structural genes modulating anthocyanin contents in C. reticulata have been unveiled. Our results will help in the development of Camellia varieties with specific flower color and quality.